Design and fabrication of N-ISFET using SI3N4/SIO2 structure for PH measurement - Nur Syuhada Md. Desa (Institute of Nano Electronic Engineering, 2013)
The objective of this research is to design, fabricate and test Ionic Sensitive Field Effect Transistor (ISFET) for pH measurement.